Nondigestible carbohydrates and digestive health - Aimutis, William R.; Paeschke, Teri M. (IFT Press series, 2011)
Featuring authors from academia as well as industry, this book provides a broad view of carbohydrates influencing digestive health. Part 1 is a general overview of carbohydrates that function as prebiotics or fermentable carbohydrates. Part 2 is a more in depth examination of specific carbohydrates for digestive health and applications